Microglia Play an Essential Role in Synapse Development and Neuron Maturation in Tissue-Engineered Neural Tissues - Zhu, Huimin; Qiao, Xin; Liu, Wei; Wang, Changyong; Zhao, Yuwei (Frontiers in Neuroscience, 2020)
In the process of constructing engineered neural tissues, we often use neural stem cells or primary neural cells, which can differentiate to microglia or contain microglia. However, the role of microglia plays in the construction of engineered neural tissue has not been well studied. Here, we generated a 3D engineered neural tissues by silk fibroin/collagen composite scaffolds and primary mix cortical cells. We depleted microglial cells by magnetic separation. Then we analyzed the neural growth, development, mature and synapse-related gene, and protein expressions compared to the control engineered neural tissues with the microglia-depleted engineered neural tissues. We found that the engineered neural tissues constructed by magnetic separation to remove microglia showed a decrease in the number of synaptic proteins and mature neurons. These findings link microglia to neuron and synaptic maturation and suggest the importance of microglia in the construction of engineered neural tissues in vitro